mRNA translation and proteasomal degradation in health and neurological disease - Alinny R. Isaac; Danielle Cozachenco; Beatriz de A. Wagner; Mariana G. Chauvet; Mychael V. Lourenco (Physiology, 2026)
The homeostasis of cellular proteins, i.e., proteostasis, is critical for neuronal function and brain processes. Proteostasis comprises a set of cellular mechanisms that control protein synthesis, folding, post-translational modification and degradation. Mounting evidence indicates that disruptions in such mechanisms may underlie several neurological diseases, including neurodevelopmental, neurodegenerative and psychiatric diseases. In this review, we discuss molecular pathways involved in protein synthesis and degradation that are altered in several brain diseases, possible pharmacological approaches to correct these defects, and future perspectives for the field.